2015
DOI: 10.12688/f1000research.7302.1
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of oral tongue squamous cell carcinoma identifies key variants and pathways linked to risk habits, HPV, clinical parameters and tumor recurrence

Abstract: Oral tongue squamous cell carcinomas (OTSCC) are a homogeneous group of tumors characterized by aggressive behavior, early spread to lymph nodes and a higher rate of regional failure. Additionally, the incidence of OTSCC among younger population (<50yrs) is on the rise; many of whom lack the typical associated risk factors of alcohol and/or tobacco exposure. We present data on single nucleotide variations (SNVs), indels, regions with loss of heterozygosity (LOH), and copy number variations (CNVs) from fifty-pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 43 publications
1
39
0
Order By: Relevance
“…An oncogene is ideally expected to exhibit increased expression in tumor compared to normal tissues. We identified significant elevation of SMARCD1 transcript in tumor compared to normal SCCOT samples (Figure a and Table S1c) corroborated in a previously published tumor versus matched normal SCCOT microarray gene expression dataset (Krishnan et al, ; Figure b). SMARCD1 expression was consistently higher in tumor over normal samples (Figure c) validated in several individual HNSCC subtypes as well (Figure S7) as well as other cancer types (Figure d) as determined from the Firebrowse database (firebrowse.org).…”
Section: Resultssupporting
confidence: 87%
“…An oncogene is ideally expected to exhibit increased expression in tumor compared to normal tissues. We identified significant elevation of SMARCD1 transcript in tumor compared to normal SCCOT samples (Figure a and Table S1c) corroborated in a previously published tumor versus matched normal SCCOT microarray gene expression dataset (Krishnan et al, ; Figure b). SMARCD1 expression was consistently higher in tumor over normal samples (Figure c) validated in several individual HNSCC subtypes as well (Figure S7) as well as other cancer types (Figure d) as determined from the Firebrowse database (firebrowse.org).…”
Section: Resultssupporting
confidence: 87%
“…The gene expression profiling using Illumina HumanHT-12 v4 expression BeadChips (Illumina, San Diego, CA), raw data collection and data processing using the R package lumi 7 and individual batch-correction using ComBat 8 is described previously 9 10 . The raw signal intensities from arrays were exported from GenomeStudio for pre-processing and analyzed using R. Gene-wise expression intensities for tumor and matched control samples from GenomeStudio were transformed and normalized using VST (Variance Stabilizing Transformation) and LOESS methods, respectively, using lumi 7 and top genes with least across-sample variance in expression were selected.…”
Section: Methodsmentioning
confidence: 99%
“…In the discovery and validation stage, HNSCC tumor: adjacent normal paired samples ( n =63 and n =14 respectively), were used. Previously published whole-genome microarray data 9 10 , RNA-seq data from TCGA 11 and data from individual studies in the literature were used in the discovery stage. For the validation set, 10 HNSCC tumor: normal pairs were from a completely independent cohort (which were not a part of discovery cohort) and 4 were used from the in house discovery cohort.…”
Section: Methodsmentioning
confidence: 99%
“…Aside from the TCGA dataset, which is composed primarily of white patients, large sequencing analyses have been performed on Asian patient groups from India and Singapore [4446]. Comparing the alteration frequencies in these populations has indicated that there may be significant differences in the mutation rates in CDKN2A , NOTCH1 , and PIK3CA [47].…”
Section: Subsequent Sequencing Studiesmentioning
confidence: 99%